(untitled) (El-Wahat Journal for Research and Studies, 2020)
With The Great Importance Of The New Media Today, Which Not Only Remained A Tool For Transmitting Knowledge Or Reporting News Or A Means For Recreation And Entertainment, But It Has Become An Effective Contributor To Shaping Thehuman Mind And Behavior. And His Possession Of High Capabilities In Influencing, Persuading And Guiding, And Influencing The Core Of Indigenous Cultures And The Constants Of The Local Identity, Such As Ethics, Religion, History Or Language, Which Made Him An Important And Influential Role In The Components Of The National Identity And Its Preservation Along With The Rest Of The Other Socialization Institutions, With A Focus On Local Media Which IsRepresented By Newspapers, Local Channels And Local Radio Stations, Which Are Interested In Providing A Rich And Distinct Cultural Reality From The Local Communities To Which They Belong, And Thus We See Them Contribute To Preserving Their Identity And Cohesion And Enhance Their Affiliation.Key Words - Media, Local Media, Identity, Affiliation, Local Culture